Shared CSF Biomarker Profile in Idiopathic Normal Pressure Hydrocephalus and Subcortical Small Vessel Disease - Jeppsson, Anna; Bjerke, Maria; Hellström, Per; Blennow, Kaj; Zetterberg, Henrik; Kettunen, Petronella; Wikkelsø, Carsten; Wallin, Anders; Tullberg, Mats (Frontiers in Neurology, 2022)
Introduction In this study, we examine similarities and differences between 52 patients with idiopathic normal pressure hydrocephalus (iNPH) and 17 patients with subcortical small vessel disease (SSVD), in comparison to 28 healthy controls (HCs) by a panel of cerebrospinal fluid (CSF) biomarkers. Methods We analyzed soluble amyloid precursor protein alpha (sAPPα) and beta (sAPPβ), Aβ isoforms −38, −40, and −42, neurofilament light protein (NFL), glial fibrillary acidic protein (GFAP), myelin basic protein (MBP), matrix metalloproteinases (MMP −1, −2, −3, −9, and −10), and tissue inhibitors of metalloproteinase 1 (TIMP1). Radiological signs of white matter damage were scored using the age-related white matter changes (ARWMC) scale. Results All amyloid fragments were reduced in iNPH and SSVD (p < 0.05), although more in iNPH than in SSVD in comparison to HC. iNPH and SSVD showed comparable elevations of NFL, MBP, and GFAP (p < 0.05). MMPs were similar in all three groups except for MMP-10, which was increased in iNPH and SSVD. Patients with iNPH had larger ventricles and fewer WMCs than patients with SSVD. Conclusion The results indicate that patients with iNPH and SSVD share common features of subcortical neuronal degeneration, demyelination, and astroglial response. The reduction in all APP-derived proteins characterizing iNPH patients is also present, indicating that SSVD encompasses similar pathophysiological phenomena as iNPH.